The difference between the medial and lateral posterior tibial slope is associated with greater internal tibial rotation. Issue 4 (27th April 2017) - Herbst, Elmar; Imhoff, Andreas; Irrgang, James; Anderst, William; Fu, Freddie
Aims and Objectives: : The objective of this study was to investigate the effect of lateral and medial posterior tibial slope (PTS) and meniscal slope (PMS) on in-vivo anterior tibial translation (ATT) and internal tibial rotation (IR) during downhill running on the healthy contralateral knee twenty-four months after ACL reconstruction. Materials and Methods: : Forty-two individuals (twenty-six males; mean age 21.2 ± 6.9 years) who underwent unilateral ACL reconstruction were included in this study. Morphologic parameters were measured on 3 T magnetic resonance images (MRI) using the 3D DESS sequence on the ACL reconstructed and healthy contralateral knee. Lateral and medial PTS and PMS were measured according to the method described by Hudek et al. Briefly, the tibial shaft axis was determined by connecting the centroids of two circles fitting the tibial shaft on the central sagittal MRI slice. The PTS and PMS were determined by the angle between the tibial shaft axis and the line connecting the two most proximal anterior and posterior subchondral bone and meniscal points in the center of each joint compartment. Three-dimensional in-vivo kinematics data were acquired using dynamic stereo x-ray during downhill running (3.0 m/s, 10° slope) at 150 Hz twenty-four months after unilateral ACL reconstruction. A multiple regression analysis was performed (p < .05). Results: : The lateral and medial PTS and PMS as well as the differences between the medial and lateral compartment slopes were not significantly related to ATT in the healthy contralateral knees twenty-four months after ACL reconstruction (p > .05). The lateral and medial PTS and PMS were not significantly related to peak internal tibial rotation (p > .05). However, the difference between the medial and lateral PTS as well as PMS was associated with greater internal tibial rotation (PTS: b=1.55, p < .001; PMS: b = .71, p = .02). Conclusion: : The most important finding of the present study is that the difference between the medial and lateral posterior tibial and meniscal slope are related to in-vivo internal tibial rotation during downhill running. ATT was not significantly influenced by the tibial bony and meniscal morphology. Taking into account the results of the present study, the difference between the medial and the lateral PTS and PMS may contribute to IR when an ACL injury occurs. However, the analyzed movement was a straight-ahead run without any cutting or pivoting maneuvers commonly related to ACL tears. In such motion patterns, the correlations may be even stronger compared to the results of this study.